Advanced Ultrasound Techniques for Differentiation of Benign Versus Malignant Thyroid Nodules: A Review. Issue 4 (December 2021) - Saade-Lemus, Sandra M.; Sridharan, Anush; Smitthimedhin, Anilawan; Bauer, Andrew; Cahill, Anne Marie; Darge, Kassa; Hwang, Misun
Abstract : Abstract: Grayscale ultrasound (US) is decisive in stratifying which thyroid nodules benefit from fine-needle aspiration to evaluate for malignancy. Unfortunately, a significant percentage of nodules remain indeterminate. Herein, we review the clinical considerations and diagnostic accuracy of advanced US, Doppler US, contrast-enhanced US, and US elastography techniques in the evaluation of indeterminate nodules. We conclude that these techniques may be used in combination with grayscale US to improve the assessment of lesion vascularity and tissue property.